Design, manufacture and investigation of cracking efficiency of a stone cracking machine with periodic loading and sloping jaw - Tosun, N.; Özler, L.; Lale, Ş. (My University, 2001)
In this study, a stone cracking machine with periodic loading, and a shaky and sloping jaw which breaks apricot and almond stones was designed and manufactured. For determining the cracking efficiency of the stone cracking machine, the apricot stones were cracked under dry and different wetting periods (1, 2, 3 and 4 hours) and jaw clearances (8.5, 9.5, 10.5 and 11.5 mm). The results obtained at the end of this study were compared with a similar type of stone cracking machine.
Periyodik Y-dsuklemeli ve E?ik Çeneli Çekirdek Kirma Makinasinin Tasarimi, Imalati ve Kirma Verimlili?inin Araştirilmasi
Keywords: Apricot and almond; Stone cracking machine